Adherence to Vegetarian Diet and Weight Loss: A Meta-Analysis: Adherence to Vegetarian Diet and Weight Loss: A Meta-Analysis - Demirci, Ülkü; Kaptanoğlu, Ayşegül (Progress in Nutrition, 2022)
Background Veganism and vegetarianism, which are becoming popular worldwide, are not only a diet but a lifestyle, a philosophy of life, and an ethical approach. A vegetarian diet is thought to be the solution to the increasing food requirements of the growing population. In this meta-analysis, we evaluated the correlation between a vegetarian diet and weight loss. Methods For the meta-analysis, PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed. We conducted a comprehensive review of the literature published in PubMed, Science Direct, and ResearchGate databases. Only randomized controlled trials and cohort studies published after 2007 were included in the meta-analysis if they reported the results on weight loss and contained appropriate statistical analysis data. Results The meta-analysis included 11 studies comprising of 934 participants, of which 10 were randomized controlled trials, and 1 was a cohort study. Applying the random effects model, it was concluded that compliance with the various types of vegetarian diets had a positive effect on weight loss. The effect size of the relation between vegetarian diet and weight loss was 0.954. It is between the lower limit (0.393) and the upper limit (1.515) values for the effect sizes of the relevant studies in the 95% confidence interval. There was no publication bias as the circles (representing each study) shown in the Funnel plot graph were spread symmetrically around the vertical line in the middle. Conclusions The vegetarian diets (vegan and lacto-ovo vegetarian diets) had beneficial effects on weight loss. One possible reason responsible for weight loss could be the varied nutritional composition, for example, high fiber and low protein diet. However, further interventional studies with vegetarian diets are warranted to investigate their long-term effects and clinical implications on weight loss.